Instability in suspensions oscillating along narrow channels (LACCEI, 2024)
The addition of solid particles to a fluid can change significantly the way it flows. This is important in several practical situations like landslides produced by heavy rain, waste treatment and blood flow. In some cases, the presence of solid particles has been shown to accelerate mixing in viscous flows through small channels. In this work, we show that oscillatory flow induces an instability characterized by particle motion transverse to the main flow, which could help improve mixing. We perform experiments with non-Brownian spherical particles (diameter 40 µm) suspended in a viscous fluid subject to square-wave oscillations inside a channel of rectangular cross-section (gap 1 mm, width 10 mm). Using fluorescence we visualize and track the particles in a plane across the gap and along the length. After a number of oscillations, we observe small but significant displacements of the particles across the gap. These displacement have oscillatory and long-term drift components, both spatially periodic along the flow direction. The latter may account for the transverse deformation of a high particle volume fraction region present in the center of the channel. Finally, we define and characterize an onset time for this instability as a function of the oscillation amplitude and the volume fraction.